2022
DOI: 10.1021/jacs.2c03421
|View full text |Cite
|
Sign up to set email alerts
|

Enlightening the Alkali Ion Role in the Photomagnetic Effect of FeCo Prussian Blue Analogues

Abstract: FeCo Prussian blue analogues of general formula A x Co y [Fe­(CN)6] z are responsive, non-stoichiometric materials whose magnetic and optical properties can be reversibly switched by light irradiation. However, elucidating the critical influence of the inserted alkali ion, A+, on the material’s properties remains complicated due to their complex local structure. Here, by investigating soluble A ⊂ [Fe4–Co4] cyanido cubes (A = K, Rb, and Cs), both accurate structural and electronic information could be obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 81 publications
(124 reference statements)
1
9
0
Order By: Relevance
“…These peaks located below the open-circuit potential are ascribed to the successive reduction of the four Fe III ions. The separation of the Fe-redox waves thus suggests an electronic communication through the cyanide bridges between two distant centers, as previously observed for most cubes. , No additional redox waves are present between −1.5 and 1.8 V. Thus, Cs⊂{TpFe 4 -Ni 4 } seems to be stable upon reduction and oxidation, as the four redox waves stay well-defined upon cycling. In contrast, the empty cube {TpFe 4 -Ni 4 } (Figure S8) seems to exhibit weaker electronic communication: the voltammogram of the {TpFe 4 -Ni 4 } in CH 3 CN shows undefined, merged redox waves with an approximated redox potential of 0.25 V, when recorded between 0.0–1.0 V. Supplementary measurements (Figures S8 and S9) with different windows and various cycles suggests that the empty procube is also stable.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…These peaks located below the open-circuit potential are ascribed to the successive reduction of the four Fe III ions. The separation of the Fe-redox waves thus suggests an electronic communication through the cyanide bridges between two distant centers, as previously observed for most cubes. , No additional redox waves are present between −1.5 and 1.8 V. Thus, Cs⊂{TpFe 4 -Ni 4 } seems to be stable upon reduction and oxidation, as the four redox waves stay well-defined upon cycling. In contrast, the empty cube {TpFe 4 -Ni 4 } (Figure S8) seems to exhibit weaker electronic communication: the voltammogram of the {TpFe 4 -Ni 4 } in CH 3 CN shows undefined, merged redox waves with an approximated redox potential of 0.25 V, when recorded between 0.0–1.0 V. Supplementary measurements (Figures S8 and S9) with different windows and various cycles suggests that the empty procube is also stable.…”
Section: Resultssupporting
confidence: 66%
“…These cubic cages can demonstrate remarkable photomagnetic and electrochromic properties. , Interestingly, our studies have shown that theses cyanido-cages were stable in organic solvents . To date, different cubes have been obtained and most of them bear tripodal facial blocking ligands of the scorpionate family. One aspect of our current research is to further explore the versatility of these cyanido-based cubes chemistry. For example, we recently showed that using a ditopic Tp-based ligand could lead to polymeric materials made of switchable cubic units .…”
Section: Introductionmentioning
confidence: 95%
“…[8][9][10][11] Photo-magnets are special class of magnetic materials for which light acts as an external stimulus for switchable magnetic behavior. [12][13][14][15] This phenomenon was observed for many years in metals (Cu, Al) and metal oxides (ferrites, garnets), after that Prussian Blue analogs (PABs) was introduced by Hashimoto and coworkers as an efficient photomagnet in late 90s. [16][17][18] More recently, a new class of inorganic-organic hybrid material had been developed by incorporating photochromic moiety into 3d-4f heterobimetallic complexes that show photomagnetism at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining good-quality crystals has been challenging. 5,8 In 2008, Holmes and his colleagues reported the first Fe/Co cube complex, 5 [(pzTp)Fe(CN) 3 Co( TpEtOH )] 4 [ClO 4 ] 4 ·13DMF·4H 2 O ( 1 0 ), with ETCST properties (pzTp − = tetra(pyrazolyl)borate; TpEtOH = 2,2,2-tris(pyrazol-1-yl)ethanol, Scheme 1). This complex exhibits reversible and steep thermally induced ETCST at 250 K, and shows a long-lived photo-induced metastable state with the characteristic T relax = 180 K. Most recently, Lescouëzec and co-workers reported a family of alkali-inserted [Fe 4 Co 4 ] cubes with the Tp − (hydrotris(pyrazol-1-yl)borate) and pzTp − serving as the capping ligands on the Fe and Co sites, 8 d respectively, denoted as A⊂[Fe 4 Co 4 ] (A + = K + , Rb + , or Cs + ).…”
Section: Introductionmentioning
confidence: 99%